Systematic Literature Review: Reframing Riverbank Erosion as a Contextual Learning Tool in Environmental Education - Sulistiawaty Sulistiawaty; Rusnita Rusnita; Erma Suryani Sahabuddin; Eka Apriyanti (Madrasah Tsanawiyah DDI Cilellang, 2026)
Riverbank erosion is a significant environmental issue that affects ecological systems, socioeconomic conditions, public health, and community resilience. Despite its widespread impacts, its potential as a contextual learning resource in environmental education has received limited scholarly attention. This study aims to synthesize existing evidence on the impacts of riverbank erosion and examine how the phenomenon can be reframed as a contextual learning medium within environmental education. A Systematic Literature Review (SLR) adapted from the PRISMA guidelines was conducted using articles retrieved through Publish or Perish from the Scopus database. Using the keywords “riverbank erosion,” “contextual learning,” and “environmental education,” the selection process resulted in 10 relevant articles, which were analyzed through qualitative descriptive techniques. The findings reveal that riverbank erosion contributes to environmental degradation, damage to land and settlements, population displacement, and increased socioeconomic vulnerability. More importantly, this review highlights the educational value of riverbank erosion as an authentic environmental context that supports contextual learning, place-based learning, and environment-based learning approaches. By synthesizing evidence across environmental and educational studies, this review provides a conceptual linkage between local environmental challenges and meaningful learning experiences. The findings suggest that integrating riverbank erosion issues into environmental education can foster environmental literacy, critical thinking, and students’ awareness of sustainability challenges, while offering educators a framework for connecting real-world environmental problems with classroom learning.